Microcrinoids from the lower and middle Albian of the Anglo-Paris Basin (southern England, UK, Seine Maritime, Pas de Calais and Aube, France). (November 2021) - Gale, Andy; Matrion, Bertrand
Abstract: Microcrinoids of the family Roveacrinidae Peck, 1943 are described from lower and middle Albian clays of the Anglo-Paris Basin (Seine Maritime, Pas de Calais and Aube, France; Kent and Bedfordshire, UK). They are referred to two subfamilies - the Orthogonocrininae Gale, 2019 and the Plotocrininae Gale, 2020. Orthogonocrinines include the long-ranging (middle Albian-lower Cenomanian) species Orthogonocrinus apertus Peck, 1943, and Styracocrinus peracutus (Peck, 1955), known from Texas, USA, Morocco, the UK and France, and two stratigraphically successive species of the genus Hyalocrinus, H. magniezii Destombes, 1984 and H. bulliensis Destombes, 1984, known only from the lower and middle Albian of the UK and France. Plotocrinines include two middle Albian species, Plotocrinus distinctus Peck, 1943 and P. rashallae Gale, 2020, known from France and Texas, and the new Calvaticrinus gen. nov., type species Plotocrinus monocarinatus Destombes, 1984. Calvaticrinus gen. nov., known only from the Anglo-Paris Basin, forms an evolutionary lineage of, successively, C. integer (Hess, 2010) – C. monocarinatus- C. subplanatus (Destombes, 1984) through the lower and middle Albian. The Plotocrinus species allow correlation of the Anahoplites intermedius Zone of northwest Europe to the lower Manuaniceras carbonarium Zone of Texas. The new material represents the oldest roveacrinids known from three-dimentsional material and forms the basis of a phylogenetic analysis of the Roveacrinidae.